can someone check if this is correct
1) does \(\displaystyle -4\sqrt{6}\) - \(\displaystyle \sqrt{6}\) = -\(\displaystyle 4\sqrt{6}\)?
2) \(\displaystyle -9\sqrt{27}\) = \(\displaystyle 27\sqrt{3}\)
3) \(\displaystyle \sqrt[3]{3}\) * \(\displaystyle \sqrt[3]{-20}\) = \(\displaystyle \sqrt[3]{3}\) * \(\displaystyle -2\sqrt[3]{5}\) = \(\displaystyle 2\sqrt[3]{15}\)
1) does \(\displaystyle -4\sqrt{6}\) - \(\displaystyle \sqrt{6}\) = -\(\displaystyle 4\sqrt{6}\)?
2) \(\displaystyle -9\sqrt{27}\) = \(\displaystyle 27\sqrt{3}\)
3) \(\displaystyle \sqrt[3]{3}\) * \(\displaystyle \sqrt[3]{-20}\) = \(\displaystyle \sqrt[3]{3}\) * \(\displaystyle -2\sqrt[3]{5}\) = \(\displaystyle 2\sqrt[3]{15}\)